Effect Of Smoking Behaviour and The BMI On Ph Levels Of Saliva and Salivary Amylase Activity Among Male Students - Yurnaliza (International Journal of Ecophysiology, 2022)
Smoking behaviour has a negative impact on health, especially oral health. One of the motivations for consuming tobacco cigarettes is stress condition. Many believe that smoking could reduce their stress. We are using purposive random sampling targeting male students who smoke at the faculty of social and political science. We find 40 individual smoking students as respondents. We measure the pH levels of saliva using universal indicators and then salivary amylase activity from the decrease of substrate (amylum) concentration. Here we find that smoking students have significantly more low salivary pH levels and also salivary amylase activity than control (non-smoking students). This could be an early diagnosis of the oral health issue. However, stress conditions could be indicated by relatively high salivary amylase activity. Our result predicted that smoking perhaps reduces the stress of the students because smoking lowers the salivary amylase rate. Moreover, stress conditions do not influence the saliva flow rate. We also use questionnaires to collect body weight and height to measure the BMI (Body mass index). The BMI data also shows most of the smoking student has a normal category of BMI. Nevertheless, there are no significant differences in Salivary pH levels and amylase activity among the BMI category. A previous study also reported that BMI has no correlation with saliva flow rate. We suggest the university should give education about the negative effect of smoking